Influence of Frontier Capital Markets Interdependence and Efficiency on Shaping Investment Strategy Under the Financial Crisis Conditions - Damir Becirovic; Emira Kozarevic (Economic Review: Journal of Economics and Business, 2018)
This research analyzes interdependence and low efficiency of the selected capital markets in the period before and after the escalation of the global financial crisis. The aim is to show, based on the obtained results, the position that can be taken by potential investors in frontier capital markets of the Western Balkan countries. The sample included the daily values of the selected stock market indices for the period October 04, 2005 to October 25, 2012. The results showed that during the crisis potential benefits of international diversification based on investments in the observed frontier capital markets decrease as the correlations among capital markets during the crisis are higher than expected, which is marked as the “contagion effect”. In terms of low efficiency, it can be concluded that the results for the period before the crisis are expected, meaning that all the selected capital markets of the Western Balkans were inefficient. Efficiency tests for the period after the escalation of the crisis show somewhat contradictory results due to the characteristics of these markets and the effect of exogenous shock such as the financial crisis.
Keywords: G01; G14; G15; 330; frontier capital markets; investment strategy; efficient market hypothesis; interdependence of capital markets